Kajian takhrij hadis sahih riwayat bukhari dan muslim dalam bab aqidah dan keimanan - Wan Embong, Wan Hassan; Ruskam, Aminuddin; Mohamed, Ahmad Kilani (UTM, 2003)
To be guided in this life, Muslims must always refer to the right references. The second authentic source in Islam is hadith. However the authenticity of hadiths were under severe scrutiny during the golden edge of Islam. Since the source had been manipulated by hadith fabricators. Hence, the importance of takhrij al-hadith emerge in order to solve the problem of separating between the authentic and fabricated hadith. This research is purposely done to collect hadiths on iman as narrated and agreed upon by Imam Bukhari and Muslim. These hadiths had been classified into various important subtopics. The data is stored in computer together with their translations for easy finding and reference.